Synthesis of a Redox-Active NNP-Type Pincer Ligand and Its Application to Electrocatalytic CO2 Reduction With First-Row Transition Metal Complexes - Talukdar, Kallol; Issa, Asala; Jurss, Jonah W. (Frontiers in Chemistry, 2019)
We report the synthesis of a rigid phosphine-substituted, redox-active pincer ligand and its application to electrocatalytic CO2 reduction with first-row transition metal complexes. The tridentate ligand was prepared by Stille coupling of 2,8-dibromoquinoline and 2-(tributylstannyl)pyridine, followed by a palladium-catalyzed cross-coupling with HPPh2. Complexes were synthesized from a variety of metal precursors and characterized by NMR, high-resolution mass spectrometry, elemental analysis, and cyclic voltammetry. Formation of bis-chelated metal complexes, rather than mono-chelated complexes, was favored in all synthetic conditions explored. The complexes were assessed for their ability to mediate electrocatalytic CO2 reduction, where the cobalt complex was found to have the best activity for CO2-to-CO conversion in the presence of water as an added proton source.